THE STATE OF THE IMMUNE SYSTEM AND LABORATORY DIAGNOSIS OF TOXOPLASMOSIS - Kudratova Z.E.; Mukhamadieva L.A.; Sa'dullaev S.E. (Journal of new century innovations, 2023)
Abstract. Toxoplasmosis is a parasitic disease characterized by a predominantly latent or chronic course, which affects the nervous system, reticuloendothelial organs, muscles, myocardium and eyes. About 30% of the world's population is infected with toxoplasmosis.